Playing with signs: A semiotic interpretation of classic music - Agawu, Kofi (Princeton Princeton university press, 1991)
Of all the repertories of Western Art music, none is as explicitly listener-oriented as that of the late eighteenth and early nineteenth centuries. Yet few attempts to analyze the so-called Classic Style have embraced the semiotic implications of this condition. Playing with Signs proposes a listener-oriented theory of Classic instrumental music that encompasses its two most fundamental communicative dimensions: expression and structure. Units of expression, defined in reference to topoi, are shown here to interact with, confront, and merge into units of structure, defined in terms of the rhetorical conventions of beginning, continuing, and ending. The book draws on examples from works by Mozart, Haydn, and Beethoven to show that the explicitly referential, even theatrical, surface of Classic music derives from a play with signs. Although addressed primarily to readers interested in musical analysis, the book opens up fruitful avenues for further research into musical semiotics, aesthetics, and Classicism.